2014
DOI: 10.1111/hdi.12204
|View full text |Cite
|
Sign up to set email alerts
|

Role of turmeric in oxidative modulation in end‐stage renal disease patients

Abstract: Oxidative stress is considered as a major player in uremia-associated morbidity and mortality in hemodialysis (HD) patients. The aim of this study was to evaluate the effects of turmeric on oxidative stress markers in HD patients. This study was a prospective and double-blind randomized clinical trial. Fifty HD patients aged 18-60 years were recruited after fulfilling the inclusion criteria. Patients were randomly categorized into 2 groups: trial group received turmeric and control group received placebo for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
1
41
1
Order By: Relevance
“…Activities of GPx, GR and CAT in red blood cells increased in both groups, the ratio of CAT increment was significantly higher in the trial group. Furthermore, a significant increment in albumin plasma level in the trial group was observed [37]. Therefore, turmeric attenuates oxidative stress and renal damage in hemodialysis patients.…”
Section: Curcuminmentioning
confidence: 79%
See 2 more Smart Citations
“…Activities of GPx, GR and CAT in red blood cells increased in both groups, the ratio of CAT increment was significantly higher in the trial group. Furthermore, a significant increment in albumin plasma level in the trial group was observed [37]. Therefore, turmeric attenuates oxidative stress and renal damage in hemodialysis patients.…”
Section: Curcuminmentioning
confidence: 79%
“…Moreover, clinical trials have been conducted to evaluate the effect of turmeric on DN [36,37]. In a randomized, double-blind and placebo-controlled study, patients with DN received turmeric (22.1 mg of curcumin, three times a day) for 2 months.…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of interventions were investigated including pomegranate juice (standardized to 0.7 mmol/L polyphenols) [ 26 , 36 , 37 ], pomegranate extract (standardized to 600–755 mg gallic acid equivalents), cacao (900 mg cocoa-flavanols) [ 28 ], turmeric (22.1 mg curcumin) [ 27 , 38 ], grape (500 mg total polyphenols) [ 25 ], green tea (455 mg total catechins) [ 39 ], and soy (26–54 mg isoflavones) ( Table 2 ) [ 40 , 41 , 42 , 43 ]. The duration of the study interventions varied from an acute, one day study [ 26 ] to 12 months [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In haemodialysis supplementation studies, key vitamins have demonstrated improvements in (non-polyphenol) antioxidant activity, such as Vitamin C [ 22 ] and Vitamin E supplementation [ 23 , 24 ]. While other polyphenol-rich interventions have shown promise to control oxidative stress and ameliorate inflammation in ESKD patients, for example, grape juice powder [ 25 ], pomegranate juice [ 26 ], turmeric [ 27 ], and cocoa flavanols [ 28 ].…”
Section: Introductionmentioning
confidence: 99%